Separating liquid and process for separating and recycling components in metal-inorganic matter composite electrode group
By separating the lithium battery electrode components at room temperature using a separation solution composed of oxalic acid and acetic acid, the problems of low recovery rate and high pollution risk in traditional technologies are solved, and efficient and environmentally friendly electrode material separation and recovery are achieved, reducing processing costs.
Patent Information
- Application Number
- CN202510719398.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-12
AI Technical Summary
Traditional waste lithium battery material recycling technology has the disadvantages of low recovery rate, high pollution risk, lengthy process and cost disadvantages. It lacks flexible adaptability and makes it difficult to efficiently separate and recycle battery cell components.
A separation liquid composed of oxalic acid and acetic acid, combined with deionized water, with a pH of 0.5-2, is used as the separation liquid. Dynamic stirring is used to separate the positive electrode and the current collector at room temperature. Combined with overflow weir flotation and screening technology, the positive and negative electrode materials are separated and purified.
Efficient separation of all components is achieved at room temperature, the positive electrode material recovery rate is greater than 96%, aluminum impurities are less than 60ppm, copper impurities are less than 25ppm, the current collector loss rate is less than 1%, the processing cost is reduced by 40%, the generation of toxic gases is avoided, and it is environmentally friendly and efficient.
Smart Images

Figure CN120637651A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of waste lithium battery material recycling, and in particular to a separation liquid and a component separation and recovery process in a metal-inorganic composite electrode group. Background Art
[0002] Traditional waste lithium battery material recycling technology faces the following core problems:
[0003] 1. Environmental and efficiency bottlenecks in hydrometallurgy and pyrometallurgy
[0004] Wet processes rely on strong acids and alkalis to dissolve materials, leading to equipment corrosion (e.g., the risk of hydrogen explosions caused by NaOH in CN109004306A) and the generation of heavy metal wastewater. Fire processes require high-temperature calcination, consume high energy, and can only recover low-purity metal oxides, unable to process organic matter. Both processes carry the risk of secondary pollution.
[0005] 2. The economic and environmental contradictions of the organic solvent method
[0006] Although solvents such as NMP can dissolve binders (such as PVDF), they are expensive and the residual solvent in the current collector after separation requires advanced treatment, which increases the discharge of organic waste liquid (for example, the CN109713393A process produces mixed materials, which require complex sorting);
[0007] 3. Disadvantages of mechanical crushing and pyrolysis technology
[0008] Mechanical methods are prone to mixing in metal fragments (e.g., aluminum content > 200ppm), reducing the reuse value of the material; pyrolysis requires high temperatures to decompose the binder, releasing toxic gases such as HF (e.g., CN106505271A), resulting in high tail gas treatment costs;
[0009] 4. Insufficient separation agent selectivity and process complexity
[0010] Traditional acid-base reagents react violently, corroding the current collector (such as dissolving aluminum foil), destroying the structure of the active material, and requiring multi-stage treatment (such as the three-stage stripping agent process in CN116136022A), generating sulfur-containing wastewater, and having poor economic efficiency;
[0011] 5. Shortcomings in process compatibility and intelligence
[0012] Battery chemical systems are diversified (ternary, iron-lithium, solid-state batteries, etc.), existing technologies lack flexible adaptability, and disassembly relies on manual labor, which is inefficient; the recycling technology of smart components (sensors, self-healing materials) has not yet made a breakthrough, resulting in serious waste of resources. Summary of the Invention
[0013] The technical problem to be solved by the present invention is that traditional technologies generally have problems such as low recovery rate (aluminum / copper foil is difficult to preserve), high pollution risk, lengthy process and cost disadvantages. It is urgent to develop mild, efficient and highly selective green separation agents and intelligent processes to achieve efficient collection and high-value regeneration of battery cell components. Therefore, a separation liquid and a component separation and recovery process in a metal-inorganic composite electrode group are provided to overcome the shortcomings of the above-mentioned existing technologies.
[0014] The technical solution of the present invention to solve the above technical problems is as follows:
[0015] The separation liquid comprises components of an active ingredient and deionized water, wherein the deionized water accounts for ≥95% by weight and has a pH of 0.5 to 2. The active ingredient is prepared by mixing oxalic acid and acetic acid in a mass ratio of 1:20 to 1:10.
[0016] On the basis of the above technical solution, the present invention can also be improved as follows.
[0017] Furthermore, the separation liquid components also include: polyethylene glycol.
[0018] Furthermore, the mass ratio of polyethylene glycol is 0.01% to 0.1%.
[0019] Furthermore, the pH was 0.8±0.1.
[0020] Based on the above technical solution, the present invention also provides a process for separating and recovering components in a metal-inorganic composite electrode group, using the above separation liquid, comprising the following steps:
[0021] S1. Cell disassembly: disassemble the failed lithium-ion battery to obtain the cell;
[0022] S2. Primary crushing: crush the battery cells and perform magnetic separation to obtain a mixed material containing positive and negative electrode sheets, separators and residual electrolyte;
[0023] S3, separation reaction: the mixed material is put into the separation liquid, and dynamic stirring is performed during the reaction to maintain the turbulent state of the solution. When the positive electrode coating is completely separated from the aluminum foil, the reaction is terminated;
[0024] S4, diaphragm separation: using overflow weir flotation separation diaphragm;
[0025] S5. Negative electrode screening: The remaining slurry is screened. The undersize is graphite negative electrode particles, and the oversize is a mixture containing current collector fragments and positive electrode fragments. The graphite negative electrode particles are washed and dried.
[0026] S6. Positive electrode purification: The oversize material in S5 is sieved with water, the undersize material is the positive electrode fragments, and the oversize material is the fragments containing the current collector. The undersize material is dried and crushed to obtain a positive electrode material free of other impurities.
[0027] Furthermore, the specific steps of S1 are as follows:
[0028] The failed lithium-ion battery is discharged to ≤1V, the shell is cut, and the battery core is mechanically separated in a nitrogen protection environment with an oxygen content of less than 5% to obtain the battery core.
[0029] Furthermore, the specific steps of S2 are as follows:
[0030] A double-shaft shredder is used to break the battery cells into pieces with a size of 100mm to 200mm. The steel shell fragments are then removed by magnetic separation to obtain a mixed material containing positive and negative electrode sheets, separators and residual electrolyte.
[0031] Furthermore, the specific steps of S3 are as follows: the solid-liquid ratio of the mixed material to the separated liquid is 1:(3-5).
[0032] Furthermore, in S3, the reaction temperature is 30°C ± 5°C, the reaction time is 1 min to 2 min, and the stirring speed is 100 rpm to 300 rpm.
[0033] Furthermore, the reaction temperature is 30°C ± 1°C.
[0034] Furthermore, in S5, the remaining slurry is passed through a 1 mm filter for screening.
[0035] Furthermore, the aperture of the water screen in S6 is 10 mm to 20 mm.
[0036] The beneficial effects of the present invention are:
[0037] 1) A composite system of oxalic acid and acetic acid is used. In this composite system, oxalic acid is the main component of the separation liquid. Its carboxylic acid group can effectively destroy the chemical bonds of the binder in the electrode material (such as the CF bond of PVDF). At the same time, it has a chelating effect on lithium salt residues (such as LiPF6), promoting the dissociation of the positive electrode material and the current collector. Its acidic environment (pH adjusted to 0.5-1) can accelerate the passivation reaction of the aluminum current collector and generate a protective layer to prevent excessive corrosion. Acetic acid acts as an inhibitor and forms a protective film by adsorbing on the surface of the copper current collector to reduce metal dissolution. At the same time, acetate ions can form a stable complex with copper ions in the solution. According to Le Chatelier's principle, the formation of the complex reduces the free Cu in the solution. 2+ The concentration of polyethylene glycol, an auxiliary component, is added as a dispersant. Due to the differences in the surface chemical properties of the positive and negative electrodes and the current collector, as well as the differences in the adsorption mechanisms of polyethylene glycol on different materials, the separation effect of different materials can be enhanced. The introduction of this separation liquid into the component separation and recovery process of the metal-inorganic composite electrode group enables the present invention to achieve full component separation at room temperature, reduce energy consumption by 70%, and avoid the generation of toxic gases (such as HF). Compared with traditional high-temperature pyrolysis (above 500°C), it has high efficiency.
[0038] 2) The cathode material recovery rate is greater than 96%, aluminum impurities are less than 60ppm, copper impurities are less than 25ppm, and the current collector loss rate is less than 1%;
[0039] 3) The separation liquid can be recycled three times with 10% fresh solution added each time, and the comprehensive processing cost is reduced to ¥1200 / ton battery cell, which is 40% lower than the alkaline dissolution method, and has good economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a flow chart of the component separation and recovery process in the metal-inorganic composite electrode group of the present invention;
[0041] Figure 2 This is an analysis chart of the effect of the oxalic acid-acetic acid mass ratio on the positive electrode impurity elements in Example 1;
[0042] Figure 3 This is a correlation analysis diagram of the dissolution rate / recovery rate and the acetic acid content in Example 1;
[0043] Figure 4 This is the SEM image of the lithium iron phosphate positive electrode recovered in Example 1;
[0044] Figure 5 This is an analysis chart of the effect of the polyethylene glycol mass ratio on the positive electrode recovery rate in Example 2;
[0045] Figure 6 The figure is a correlation analysis diagram between the recovery rate and the oxalic acid content in Example 3. DETAILED DESCRIPTION
[0046] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0047] Example 1
[0048] Separation process of oxalic acid-acetic acid complex system
[0049] The separation liquid comprises an active ingredient and deionized water, wherein the active ingredient adopts an oxalic acid-acetic acid compound system. In this embodiment, the oxalic acid mass concentration is fixed at 0.25wt%, and the acetic acid concentration is adjusted to achieve a mass ratio gradient (1:20 to 1:10). A total of 10 groups of experiments are set up. Specific data are shown in Table 1. The pH is adjusted to 0.8±0.1, and oxalic acid dominates the acidic environment.
[0050] The process for separating and recovering components in a metal-inorganic composite electrode group includes the following steps:
[0051] S1. Cell disassembly: discharge the failed lithium-ion battery to ≤1V, cut the shell, and mechanically separate the cell in a nitrogen protection environment with an oxygen content of <5% to obtain the cell;
[0052] S2. Primary crushing: The battery cells are crushed into pieces of 150 mm in size using a double-shaft shredder. The steel shell fragments are then removed by magnetic separation. After magnetic separation, the residual steel shell fragments are less than 0.5%, thereby obtaining a mixed material containing positive and negative electrode sheets, separators, and residual electrolyte.
[0053] S3. Separation reaction: The mixed material is added to the separation liquid at a solid-to-liquid ratio of 1:(3-5). During the reaction, dynamic stirring is performed to maintain the solution in a turbulent state. The reaction temperature is 30°C ± 1°C, the reaction time is 90 seconds (since the aluminum foil is smooth and silvery white, the reaction is basically completed when the positive electrode coating and the aluminum foil are completely separated). The stirring speed is 100 rpm to 300 rpm;
[0054] S4, diaphragm separation: overflow weir flotation separation diaphragm, due to the low density of diaphragm material (PP / PE) (0.9g / cm 3 ~1.1g / cm 3 ), so this characteristic can be used to achieve flotation separation through overflow weir design, and the purity after salvage and drying can reach 99.2%;
[0055] S5. Negative electrode screening: The remaining slurry is screened through a 1 mm filter screen. The undersize is the graphite negative electrode particles, and the oversize is a mixture of current collector fragments and positive electrode fragments. The graphite negative electrode particles are washed and dried.
[0056] S6. Positive electrode purification: The oversize material in S5 is passed through a 10mm to 20mm water sieve, and the undersize material is the positive electrode fragments (<10mm). The oversize material is the fragments containing the current collector, and the undersize material is dried and crushed to obtain a positive electrode material free of other impurities.
[0057] After screening, the purity and impurity content of each component are tested
[0058] Table 1: Correlation data between concentration gradient and impurity element content
[0059]
[0060]
[0061] Figure 2 The effect of the oxalic acid-acetic acid mass ratio on the impurity elements in the positive electrode is shown in the figure. The horizontal axis represents the experimental group (i.e., indirectly corresponding to different mass ratios of oxalic acid-acetic acid); the vertical axis represents the impurity content / ppm; the positive electrode Cu impurity residual lithium inhibition: acetic acid has the best protection for Cu at a ratio of 1:20 (copper residue 20ppm), and its mechanism is acetate and Cu 2+ Form stable complexes (such as Cu(CH3COO)2(H2O)2) to reduce free Cu 2+Concentration and oxalic acid-acetic acid mass ratio have little effect on the residual Al impurities in the positive electrode. Figure 4 This is the SEM image of the recycled lithium iron phosphate positive electrode. It can be seen from the figure that the morphology and particle size meet the standards of lithium iron phosphate positive electrode materials.
[0062] Figure 3 Figure 3 is the correlation between the dissolution rate / recovery rate and the experimental group (i.e., indirectly corresponding to different mass ratios of oxalic acid to acetic acid). The trend of Al dissolution rate in the current collector is as follows: as the proportion of acetic acid decreases (the mass ratio increases), the Al dissolution rate increases significantly. When the mass ratio of oxalic acid to acetic acid is 1:20, the Al dissolution rate is only 0.8%, while when the mass ratio of oxalic acid to acetic acid is 1:9, the Al dissolution rate reaches 7.3%, indicating that the passivation protection effect of acetic acid on Al weakens as its concentration decreases.
[0063] The conclusion is as follows:
[0064] 1. Optimal quality ratio: Oxalic acid: acetic acid = 1:20 for the best overall performance, lower Al / Cu impurities in the positive electrode, and a positive electrode purity of 98.5%;
[0065] 2. Critical threshold: When the mass ratio exceeds 1:11, the dissolution of the current collector Cu accelerates;
[0066] 3. If considering the economy and recycling effect, a ratio of about 1:11 is more reasonable.
[0067] Example 2
[0068] Enhanced separation process of oxalic acid-acetic acid complex system + polyethylene glycol
[0069] The separation liquid comprises an active ingredient, deionized water, and polyethylene glycol. The active ingredient is an oxalic acid-acetic acid compound system, with a fixed oxalic acid concentration of 0.25 wt% and a mass ratio of oxalic acid to acetic acid of 1:11. 0-0.1 wt% of polyethylene glycol 200 is additionally added as a dispersant. A total of 6 groups of experiments were conducted. Specific data are shown in Table 2. The pH was adjusted to 0.8±0.1, and oxalic acid dominated the acidic environment.
[0070] The process for separating and recovering components in a metal-inorganic composite electrode group includes the following steps:
[0071] S1. Cell disassembly: discharge the failed lithium-ion battery to ≤1V, cut the shell, and mechanically separate the cell in a nitrogen protection environment with an oxygen content of <5% to obtain the cell;
[0072] S2. Primary crushing: The battery cells are crushed into pieces of 150 mm in size using a double-shaft shredder. The steel shell fragments are then removed by magnetic separation. After magnetic separation, the residual steel shell fragments are less than 0.5%, thereby obtaining a mixed material containing positive and negative electrode sheets, separators, and residual electrolyte.
[0073] S3. Separation reaction: The mixed material is added to the separation liquid at a solid-liquid ratio of 1:(3-5). During the reaction, dynamic stirring is performed to maintain the solution in a turbulent state. The reaction temperature is 30°C ± 1°C, the reaction time is 90 seconds, and the stirring speed is 100 rpm to 300 rpm.
[0074] S4, diaphragm separation: using overflow weir flotation separation diaphragm;
[0075] S5. Negative electrode screening: The remaining slurry is screened through a 1 mm filter screen. The undersize is the graphite negative electrode particles, and the oversize is a mixture of current collector fragments and positive electrode fragments. The graphite negative electrode particles are washed and dried.
[0076] S6. Positive electrode purification: The oversize material in S5 is passed through a 10mm to 20mm water sieve, and the undersize material is the positive electrode fragments (<10mm). The oversize material is the fragments containing the current collector, and the undersize material is dried and crushed to obtain a positive electrode material free of other impurities.
[0077] After screening, the purity and impurity content of each component are tested
[0078] Table 2: Correlation data between concentration gradient and impurity element content
[0079]
[0080]
[0081] Figure 5 The effect of the polyethylene glycol mass ratio on the positive electrode recovery rate is shown in Figure 2, where the horizontal axis represents the experimental group number (i.e., indirectly corresponding to different polyethylene glycol mass ratios); the vertical axis represents the impurity content / ppm. According to data analysis, the positive electrode recovery rate is improved: when the polyethylene glycol mass ratio is greater than 0.06wt%, the positive electrode recovery rate can reach a maximum of 97.7%, and the polyethylene glycol mass ratio has little effect on the Cu / Al impurity residue.
[0082] The conclusion is as follows: Adding polyethylene glycol as a dispersant can enhance the separation effect of different materials and increase the positive electrode recovery rate through the differences in the adsorption mechanisms of polyethylene glycol on different materials.
[0083] Example 3
[0084] Enhanced separation process of oxalic acid-acetic acid complex system + polyethylene glycol
[0085] The separation liquid comprises an active ingredient and deionized water. The active ingredient is an oxalic acid-acetic acid compound system with a mass ratio of oxalic acid to acetic acid of 1:11 to 5:11, i.e., a high-proportion oxalic acid system is optimized. Five groups of experiments were conducted, and the specific data are shown in Table 3. The pH was adjusted to 0.8±0.1, and the oxalic acid dominated the acidic environment.
[0086] The process for separating and recovering components in a metal-inorganic composite electrode group includes the following steps:
[0087] S1. Cell disassembly: discharge the failed lithium-ion battery to ≤1V, cut the shell, and mechanically separate the cell in a nitrogen protection environment with an oxygen content of <5% to obtain the cell;
[0088] S2. Primary crushing: The battery cells are crushed into pieces of 150 mm in size using a double-shaft shredder. The steel shell fragments are then removed by magnetic separation. After magnetic separation, the residual steel shell fragments are less than 0.5%, thereby obtaining a mixed material containing positive and negative electrode sheets, separators, and residual electrolyte.
[0089] S3. Separation reaction: The mixed material is added to the separation liquid at a solid-liquid ratio of 1:(3-5). During the reaction, dynamic stirring is performed to maintain the solution in a turbulent state. The reaction temperature is 30°C ± 1°C, the reaction time is 90 seconds, and the stirring speed is 100 rpm to 300 rpm.
[0090] S4, diaphragm separation: using overflow weir flotation separation diaphragm;
[0091] S5. Negative electrode screening: The remaining slurry is screened through a 1 mm filter screen. The undersize is the graphite negative electrode particles, and the oversize is a mixture of current collector fragments and positive electrode fragments. The graphite negative electrode particles are washed and dried.
[0092] S6. Positive electrode purification: The oversize material in S5 is passed through a 10mm to 20mm water sieve, and the undersize material is the positive electrode fragments (<10mm). The oversize material is the fragments containing the current collector, and the undersize material is dried and crushed to obtain a positive electrode material free of other impurities.
[0093] After screening, the purity and impurity content of each component are tested
[0094] Table 3: Correlation data between concentration gradient and impurity element content
[0095]
[0096] Figure 6 This is a correlation analysis diagram between the recovery rate and the experimental group (indirectly corresponding to different mass ratios of oxalic acid-acetic acid). The trend of the positive electrode recovery rate is: as the proportion of oxalic acid increases, the positive electrode recovery rate gradually decreases. The oxalic acid concentration has little effect on the Al dissolution rate and the residual Al and Cu impurities in the positive electrode.
[0097] Conclusion: Oxalic acid acidity can accelerate the passivation reaction of aluminum current collector and form a protective layer to prevent excessive corrosion.
[0098] Comparative Example 1: Traditional hydrometallurgy
[0099] 1. Disassembly of battery cells: After discharging the failed lithium-ion battery to ≤1V, cut the shell with a shearing machine to separate the battery cells;
[0100] 2. Separate the electrodes: Manually peel off the positive and negative electrodes and diaphragms, and tear the electrodes into pieces of about 50 mm;
[0101] 3. Add materials and dissolve: put the positive electrode into NaOH solution and stir to dissolve, and control the reaction temperature to 80℃±5℃.
[0102] 4. Filtration and purification: Use a suction funnel to filter, and after drying, use a gauze sieve to filter out the positive electrode material.
[0103] Table 4: Correlation data between concentration gradient and impurity element content
[0104]
[0105] As the NaOH concentration increases, the dissolution rate of aluminum foil increases, the residual aluminum impurities in the positive electrode will gradually decrease, and the positive electrode recovery rate will gradually increase.
[0106] Conclusion: The recovery rate of the positive electrode of the traditional hydrometallurgical method is above 87%, which is lower than that of the present invention. At the same time, there are problems of excessive aluminum impurities and lithium element loss.
[0107] Comparative Example 2: NMP solvent method
[0108] 1. Disassembly of battery cells: After discharging the failed lithium-ion battery to ≤1V, cut the shell with a shearing machine to separate the battery cells;
[0109] 2. Separate the electrodes: Manually peel off the positive and negative electrodes and diaphragms, and tear the electrodes into pieces of about 50 mm;
[0110] 3. Dissolving the materials: Add the positive electrode into NMP and stir, and control the reaction temperature to 60℃±5℃;
[0111] 4. Centrifugal purification: Remove the aluminum foil, centrifuge the solution, and dry it to obtain the positive electrode material.
[0112] Conclusion: Since the NMP solvent method causes a large amount of positive electrode to be dispersed in NMP, the positive electrode extraction process is complicated, the recovery rate of 85% is lower than that of the present invention, the aluminum impurity is 300ppm, and the cost of NMP waste liquid treatment is relatively high.
[0113] Comparative Example 3: High-temperature pyrolysis
[0114] 1. Disassembly of battery cells: After discharging the failed lithium-ion battery to ≤1V, cut the shell with a shearing machine to separate the battery cells;
[0115] 2. Separate the electrodes: Manually peel off the positive and negative electrodes and diaphragms, and tear the electrodes into pieces of about 50 mm;
[0116] 3. High temperature pyrolysis: Place the positive electrode into a nitrogen atmosphere sintering furnace, control the reaction temperature to 500℃±5℃, and continue for 2h;
[0117] 4. Screening and purification: Use a crusher to crush, dry and then filter out the positive electrode material through a 100-mesh sieve.
[0118] Conclusion: HF gas is released (concentration>15ppm), the cost of tail gas treatment increases, and the recovery rate of positive electrode material is 75%.
[0119] Comparison of Example and Comparative Example Data
[0120]
[0121] Conclusion: The present invention achieves efficient separation of electrode components at room temperature through the oxalic acid-acetic acid composite system and classification process, with a positive electrode material recovery rate greater than 96%, aluminum impurities less than 60ppm, copper impurities less than 25ppm, current collector loss rate less than 1%, cost reduction of more than 40%, and no secondary pollution, which is significantly superior to traditional technologies.
[0122] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are illustrative and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A separation liquid, characterized in that Its components include: active ingredients and deionized water, the mass proportion of deionized water is ≥95%, the pH value is 0.5-2, and the active ingredients are prepared by mixing oxalic acid and acetic acid in a mass ratio of 1:20-1:
10.
2. The separation liquid according to claim 1, characterized in that Also includes: Polyethylene glycol.
3. The separation liquid according to claim 1 or 2, characterized in that The mass ratio of the polyethylene glycol is 0.01% to 0.1%.
4. The separation liquid according to any one of claims 1 to 3, characterized in that The pH is 0.8±0.
1.
5. A process for separating and recovering components in a metal-inorganic composite electrode group, characterized in that: Using the separation solution according to any one of claims 1 to 4, comprising the following steps: S1. Cell disassembly: disassemble the failed lithium-ion battery to obtain the cell; S2. Primary crushing: crush the battery cells and perform magnetic separation to obtain a mixed material containing positive and negative electrode sheets, separators and residual electrolyte; S3, separation reaction: the mixed material is put into the separation liquid, and dynamic stirring is performed during the reaction to maintain the turbulent state of the solution. When the positive electrode coating is completely separated from the aluminum foil, the reaction is terminated; S4, diaphragm separation: using overflow weir flotation separation diaphragm; S5. Negative electrode screening: The remaining slurry is screened. The undersize is graphite negative electrode particles, and the oversize is a mixture containing current collector fragments and positive electrode fragments. The graphite negative electrode particles are washed and dried. S6. Positive electrode purification: The oversize material in S5 is sieved with water, the undersize material is the positive electrode fragments, and the oversize material is the fragments containing the current collector. The undersize material is dried and crushed to obtain the positive electrode material.
6. The process for separating and recovering components in a metal-inorganic composite electrode assembly according to claim 5, characterized in that: The specific steps of S1 are as follows: The failed lithium-ion battery is discharged to ≤1V, the shell is cut, and the battery core is mechanically separated in a nitrogen protection environment with an oxygen content of less than 5% to obtain the battery core.
7. The process for separating and recovering components in a metal-inorganic composite electrode assembly according to claim 5, characterized in that: The specific steps of S2 are as follows: A double-shaft shredder is used to break the battery cells into pieces with a size of 100mm to 200mm. The steel shell fragments are then removed by magnetic separation to obtain a mixed material containing positive and negative electrode sheets, separators and residual electrolyte.
8. The process for separating and recovering components in a metal-inorganic composite electrode assembly according to claim 5, characterized in that: The specific steps of S3 are as follows: the solid-liquid ratio of the mixed material to the separated liquid is 1:(3-5).
9. The process for separating and recovering components in a metal-inorganic composite electrode assembly according to claim 8, characterized in that: In S3, the reaction temperature is 30°C ± 5°C, the reaction time is 1 min to 2 min, and the stirring speed is 100 rpm to 300 rpm.
10. The process for separating and recovering components in a metal-inorganic composite electrode assembly according to claim 9, characterized in that: The reaction temperature is 30℃±1℃.
Citation Information
Patent Citations
Recycling method of lithium-ion battery
CN106505271A
An efficient recovery method of waste ternary polymer lithium ion power battery material
CN109004306A
Method for separation of active material of lithium battery
CN109713393A
Stripping agent, stripping liquid composition and stripping method of waste lithium ion battery electrode material
CN116136022A